Development of genipin-crosslinked fucoidan/chitosan-N-arginine nanogels for preventing Helicobacter infection. (June 2017) - Lin, Yu-Hsin; Lu, Kun-Ying; Tseng, Ching-Li; Wu, Jui-Yu; Chen, Chien-Ho; Mi, Fwu-Long
Aim: This study aims to validate the anti- Helicobacter pylori efficacy of amoxicillin-loaded nanoparticles and nanogels with pH-responsive and site-specific drug release properties against H. pylori infection.Materials & methods: Genipin-crosslinked low molecular weight fucoidan/chitosan- N -arginine nanogels (FCSA) were prepared for targeted delivery of amoxicillin to the site of H. pylori infected AGS gastric epithelial cells.Results: The negatively charged nanogels (n-FCSA) adhered to H. pylori and exhibited pH-responsive drug release property to reduce cytotoxic effects in H. pylori infected AGS cells.Conclusion: These in vitro findings suggest that n-FCSA nanogels are potential carriers for H. pylori specific delivery of antibacterial agents, and provide the basis for further studies on the clinical use of the nanogels.